(untitled) (Research, Society and Development, 2021)
Objective: Perform phytochemical analysis of the secondary metabolisms of the root and leaf of the plant Phyllanthus Niruri L. (Stone Breaker). Methods: The experimental procedures as well as the phytochemical analysis followed the recommendations evidenced in the manual of Barbosa et al., (2001) entitled "Manual for Phytochemical and Chromotographic Analysis of Plant Extracts". The collection of the plant Phyllanthus Niruri, known as "stonebreaker", took place from March 2015 until April of the same year, in the city of Boa Vista-Roraima. The study process began with the drying of the plant for five days in an environment without interference from sunlight, then the analysis of metabolisms using parts of the leaf and root, the gross weight of the leaf was equivalent to 1.680g and the root was 0.103g. Results: It was possible to show through the experiment the presence of tannins, flavonoids. The results obtained were for tannin-positive leaf, flavonoid and for flavonoid-positive root only. Conclusion: The results help to set up a strategy to help in the search for new inputs that has in view the cost-benefit ratio and contribute to future research with medicinal plants.